Atomically Flat, 2D Edge‐Directed Self‐Assembly of Block Copolymers. Issue 3 (12th December 2022) - Kim, Jang Hwan; Jeong, Hyeon U; Yeom, Hye‐In; Han, Kyu Hyo; Yang, Geon Gug; Choi, Hee jae; Kim, Jong Min; Park, Sang‐Hee Ko; Jin, Hyeong Min; Kim, Jaeup U.; Kim, Sang Ouk
Abstract: Nanoscale shape engineering is an essential requirement for the practical use of 2D materials, aiming at precisely customizing optimal structures and properties. In this work, sub‐10‐nm‐scale block copolymer (BCP) self‐assembled nanopatterns finely aligned along the atomic edge of 2D flakes, including graphene, MoS2, and h ‐BN, are exploited for reliable nanopatterning of 2D materials. The underlying mechanism for the alignment of the self‐assembled nanodomains is elucidated based on the wetting layer alternation of the BCP film in the presence of intermediate 2D flakes. The resultant highly aligned nanocylinder templates with remarkably low levels of line edge roughness (LER) and line‐width roughness (LWR) yield a sub‐10‐nm‐wide graphene nanoribbon (GNR) array with noticeable switching characteristics (on‐to‐off ratio up to ≈6 × 10 4 ). Abstract : Atomically flat, 2D edge directed self‐assembly of block copolymers are demonstrated as sub‐10 nm nanopatterns that are remarkably well‐aligned along the atomic edge of 2D flakes, including graphene, MoS2, and h ‐BN, and they are readily exploited for nanoscale shape engineering of 2D materials. The resultant highly aligned sub‐10‐nm‐wide graphene nanoribbon exhibits superior switching characteristics (on‐to‐off ratio of ≈6 × 10 4 ).